Writing in disguise : academic life in subordination - Caesar, Terry (Ohio University Press, 1998)
Writing in Disguise is a series of increasingly personal essays that both discuss and dramatize through firsthand experience the significance of subordination in academic life, in terms of issues and structures but above all in terms of texts. Some are written: memos, rejection letters, even resignation letters. Some are not: anecdotes, protests, jokes, parodies. All of these texts have in common the imperative of disguise, represented as the most crucial consequence of dominant discourse, within which subordination might speak only by knowing its place, and write only by producing hidden transcripts. Caustic, pointed, satiric, Writing in Disguise is an engaging critique of aspects of academia involving the misuse, misappropriation, and misappreciation of verbal communication in its many guises. This book presents a series of personal essays in which the author analyzes and dramatizes the significance of subordination in academic life. Academic life is examined in terms of issues (such as sexual harassment) and structures (such as the figure of the dissertation director) but especially in terms of texts.